The Analysis of Acoustic Characteristics and Sound Absorption Coefficient of Needle Punched Nonwoven Fabrics. Issue 2 (June 2014) - Shahani, Fereshteh; Soltani, Parham; Zarrebini, Mohammad
Control of acoustical related phenomenon in environments, such as work place and residential homes, using various textile materials has gained paramount importance. Nonwoven fabrics in general are ideal acoustical insulator due to their high volume-to-mass ratio. This research examined acoustic characteristics of structured needle punched floor coverings in relation to fiber fineness, surface effect, punch density, areal density, and chemical bonding process. Sound absorption of the test samples was measured using the impedance tube method. Results indicate that fabrics produced from finer fibers absorb sound waves more efficiently. It was found that, samples with no surface effect enjoy the maximum sound absorption. This is followed by velour and cord surface effect samples. It was established that, higher levels of punch density and higher areal density caused the noise reduction coefficient (NRC) of the fabrics to be increased. It was also found that chemical finishing adversely affected the sound absorption property of the samples.